Hard road to vengeance - Johnstone, William W.; Johnstone, J. A. (Johnstone, William W. Stoneface Finnegan, 2022)
The Pinkertons believe Rollie "Stoneface" Finnegan was the best agent to ever wear the badge. So does dewy-eyed Pinkerton hopeful and sleuth-in-training Tish Gray, who's just arrived in Boar Gulch. As co-owner of Boar Gulch's Last Drop Saloon, Stoneface is content slinging booze into guts instead of bullets. But when his partner Jubal "Pops" Tennyson needs help to rescue his daughter, Stoneface saddles up to take a hard ride into hell. Their destination is Deadwood, Dakota Territory, the notorious mining town and outlaw haven where folks can dig up a gold fortune or dig their own grave. Pops' daughter is being held captive by the infamous Al Swearengen, owner of the Gem Theater, supplying whiskey, wagering, and women to the desperate, the destitute, and the dangerous. As naive, young Tish goes undercover at the Gem to find Pops' daughter, Stoneface and his partner are pinned down in the Black Hills by every trigger-happy gunslinger looking to collect the dead-or-alive bounty on Stoneface's head ...